Generalized m-Polar Fuzzy Positive Implicative Ideals of BCK-Algebras - Anas Al-Masarwah; Abd Ghafur Ahmad; G. Muhiuddin; D. Al-Kadi (Journal of Mathematics)
This study focuses on combining the theories of m-polar fuzzy sets over BCK-algebras and establishing a new framework of m-polar fuzzy BCK-algebras. In this paper, we define the idea of m-polar fuzzy positive implicative ideals in BCK-algebras and investigate some related properties. Then, we introduce the concepts of m-polar ∈,∈∨q-fuzzy positive implicative ideals and m-polar ∈¯,∈¯∨q¯-fuzzy positive implicative ideals in BCK-algebras as a generalization of m-polar fuzzy positive implicative ideals. Several properties, examples, and characterization theorems of these concepts are considered.